APOPHIS - Effects of the 2029 Earth's encounter on the surface and nearby dynamics - Valvano, G. [UNESP]; Winter, O. C. [UNESP]; Sfair, R. [UNESP]; MacHado Oliveira, R. [UNESP]; Borderes-Motta, G.; Moura, T. S. [UNESP] (Oxford University Press (OUP), 2022)
The 99942 Apophis close encounter with Earth in 2029 may provide information about asteroid's physical characteristics and measurements of Earth's effects on the asteroid surface. In this work, we analysed the surface and the nearby dynamics of Apophis. The possible effects of its 2029 encounter on the surface and environment vicinity are also analysed. We consider a 340 m polyhedron with a uniform density (1.29, 2.2, and 3.5 g cm-3). The slope angles are computed, as well their variation that arises during the close approach. Such variation reaches 4° when low densities are used in our simulations and reaches 2° when the density is high. The zero-velocity curves, the equilibrium points, and their topological classification are obtained. We found four external equilibrium points and two of them are linearly stable. We also perform numerical simulations of bodies orbiting the asteroid, taking into account the irregular gravitational field of Apophis and two extra scenarios of perturbations: the solar radiation pressure and the Earth's perturbation during the close approach. The radiation pressure plays an important role in the vicinity of the asteroid, only cm-sized particles survived for the time of integration. For densities of 2.2 and 3.5 g cm-3, a region of 5 cm radius particles survived for 30 yr of the simulation, and for 1.29 g cm-3, only particles with 15 cm of radius survived. The ejections and collisions are about 30-50 times larger when the close encounter effect is added but around 56-59 per cent of particles still survive the encounter.
Keywords: celestial mechanics; methods: numerical; minor planets, asteroids: general; planets and satellites: dynamical evolution and stability